2019
DOI: 10.2147/ott.s229231
|View full text |Cite
|
Sign up to set email alerts
|

<p>Overexpressing CCT6A Contributes To Cancer Cell Growth By Affecting The G1-To-S Phase Transition And Predicts A Negative Prognosis In Hepatocellular Carcinoma</p>

Abstract: PurposeTo determine the oncogenic role of the sixth subunit of chaperonin-containing tailless complex polypeptide 1 (CCT6A) in hepatocellular carcinoma (HCC) and address the correlation of CCT6A with clinicopathological characteristics and survival. Additionally, this study aimed to explore the effect of CCT6A on HCC cells and the underlying mechanisms.MethodsWe searched for levels of CCT6A expression in the Oncomine database and GEPIA database, which was then validated by analyzing cancer and adjacent non-can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 31 publications
3
51
0
Order By: Relevance
“…CCT6A may contribute to HCC cell proliferation by accelerating the G1-to-S transition and predicts a negative prognosis in Hepatocellular Carcinoma (20). Consistent with the previously published papers, the high expression of PSMD14 and CCT6A were found positively related to the poor prognostic of HCC patients in our research.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…CCT6A may contribute to HCC cell proliferation by accelerating the G1-to-S transition and predicts a negative prognosis in Hepatocellular Carcinoma (20). Consistent with the previously published papers, the high expression of PSMD14 and CCT6A were found positively related to the poor prognostic of HCC patients in our research.…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, the AUC value of the signature-based nomogram was nearly better than the AUC values of age, grade status and stage in 1-, 3, 5-years. Next, we further veri ed the mRNA expression of 6-genes (RBM45, PSMD1, OLA1, CCT6A , LCAT and IVD) for HCC patients in the Oncomine, TIMER, TCGA and ICGC database, which is consistent with the results of previous studies (18)(19)(20)(21). What's interesting, there are no reports of RBM45 and IVD genes in liver cancer.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, CCT intrinsically connects to all cellular processes that rely on the microtubule and actin filament components of the cytoskeleton [9,23]. Some recent studies uncover the role of CCT6A in tumor pathology [17,18,24,25]. For instance, CCT6A is upregulated in drug-resistant variants of the human melanoma cell line compared with the parental human melanoma cell line [25].…”
Section: Discussionmentioning
confidence: 99%
“…CCT6B, as a molecular chaperone involved in protein folding mediated by cytoplasmic chaperonin containing TCP-1, is currently found to be highly expressed in the testis and mucosal wounds [14,15]. As to CCT6A, a few recent data reveal that CCT6A promotes cell proliferation and metastasis in various cancers (such as NSCLC, colon carcinoma, and hepatocellular carcinoma (HCC)) [11,[16][17][18][19][20]. Besides, several clinical practices illuminate that CCT6A correlates with deteriorated tumor features and unsatisfactory prognosis in patients with several cancers (including breast cancer, HCC, and colorectal cancer).…”
Section: Introductionmentioning
confidence: 99%
“…The protein encoded by the CCT6A gene is a molecular chaperone, which is a member of the chaperone containing the TCP1 complex (CCT). It has been shown that CCT6A protein expression levels are elevated in tumor tissues of patients with hepatocellular carcinoma and that the overall survival of these patients is relatively shorter [5] . Previous studies have also con rmed that the number of mutant peptides has potential prognostic value, with somatic variants showing increased expression of CCT6A, which has clinical signi cance [6] .…”
Section: Introductionmentioning
confidence: 99%